Fraction of spectral solar radiance transmitted through snow and sea ice as measured in different depths under sea ice (transflectance) at ROV station ODEN_AO2018_910-1 - Anhaus, Philipp; Katlein, Christian; Hoppmann, Mario; Nicolaus, Marcel (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2020)
Measurements of transmitted radiance under sea ice and corresponding incident solar radiation at the surface have been performed on multi-year ice during the Oden_AO18 campaign (Arctic Ocean 2018: MOCCHA - ACAS - ICE) Central Arctic / North Pole drift station between 19 August and 13 September 2018. The radiation measurements have been performed with RAMSES spectral radiometes (TriOS, Rastede, Germany). All data are given in full spectral resolution interpolated to 1.0 nm, and integrated over the entire wavelength range (broadband, total: 320 to 950 nm). The radiance sensor (7° opening angle) was installed on the ROV. The transflectance is the ratio between transmitted radiance and incident irradiance. All times are given in UTC.